Impact of verbal feedback and started to learn some skills on the Prancing Horse - Khalid, Mayada (Journal of Physical Education, 2023)
The Thesis included five sections -The First section ( Introduction ):It includes Introduction and research importance and the importance of movement skills in ground gymnastics and how to learn it according to scientific basis represented by feedback. The researcher used two types of feedback the pronounced and written. Also it contained the problem of the research and how to limit it that the presenting of feedback does not occur according to scientific basis but it presented randomly without any organizing so it will be very weak.Aims of Research 1-Prepare a learning procedure by using of feedback (pronounced and written) in learning of some of movement skills in ground gymnastics.2-Be acquainted with the influence of feedback (pronounced and written) in learning these skills.3-Be acquainted with any styles (pronounced or written), it is more effective in learning these skills. -Research hypothesis 1-There were dissimilarities with statistics significance between before and after tests in learning some of movement skills in ground gymnastics.2-There were dissimilarities with statistics significance for the after tests results with benefit to the two experimented groups.Second Section: It deals with theoretical studies and prior studies.Third Section: Research procedureThe procedure used in the research is ( Experimental research) and the samples consist of ( 16 student ) male gender were distributed into two experimental groups .The program took ( 11 learning unit , one unit for every group weekly .Fourth section: View, analyze and discuss results.It ensures the researcher approach from results after applying a group of statistics means.Fifth Section: Results and Recommendations Results:1-The Feedback has a positive influence in presenting it.2-Types of feedback are very necessary in learning process.3-The shape of feedback has an influence in learning process. Recommendation 1-Stressing on using feedback regardless of its type in learning process. 2-Keep away from the ways that do not use feedback. 3-Basing on correcting information (written and pronounced) in the same time.